The Dark Side of Alcohol: Implications for Muscle Growth, mTOR Pathway, and Athletic Recovery - Dobosz, Anna; Zduńczyk, Wiktoria; Dubińska, Michalina; Paduch-Jakubczyk, Wiktoria; Bilska, Wiktoria; Żydek, Ada; Ciułek, Urszula (Quality in Sport, 2024)
Introduction and Objective: Alcohol is a prevalent substance in many cultures, often associated with socializing, relaxation, and even post-exercise rituals. Despite its widespread use, the effects of alcohol on muscle recovery and hypertrophy are not well understood by the general public. Emerging research suggests that alcohol may have negative health effects on these factors. Understanding the interaction between alcohol consumption and resistance training is crucial for athletes and individuals aiming to optimize their fitness outcomes. The main aim of this article is to show clinicians, patients and, above all, athletes, the negative effects of alcohol on training and leading a healthy lifestyle. Review and Methods: Review and summary of studies and meta-analysis of studies available in open-source format on Google Scholar, Web of Science and PubMed. Abbreviated Description of the State of Knowledge: Resistance training is a proven method for increasing muscle mass and strength through the process of hypertrophy, where muscle protein synthesis (MPS) exceeds muscle protein breakdown (MPB). The mechanistic/mammalian target of rapamycin (mTOR) signaling pathway plays a key role in regulating MPS and hypertrophy. Summary: Alcohol has been shown to impair muscle protein synthesis, primarily through its negative effects on the mTOR signaling pathway, which is crucial for muscle growth. Additionally, alcohol disrupts sleep quality, further hindering recovery and performance.